Flexible nano-cloth-like Ag cluster@rGO with ultrahigh SERS sensitivity for capture-optimization-detection due to effective molecule–substrate interactions. Issue 34 (15th August 2022) - Cui, Yanying; Xu, Linan; Li, Haitao; Wang, Xuan; Sun, Fuwei; Wang, Huan; Guo, Xinguang; Zhang, Yihe; Gao, Hongbo; An, Qi
Abstract : Ultrahigh SERS sensitivity has been realized on a composite SERS substrate comprising Ag clusters grown on rGO-nano cloth. Abstract : Surface-enhanced Raman scattering (SERS) is a rapid and promising detection technique for trace molecules. A central goal of research in this area is to achieve the highly sensitive detection of molecules built on a systematic understanding of enhancement mechanisms. Herein, we develop a Ag cluster@rGO composite nanostructure, which utilizes strong molecular adsorption to achieve ultrahigh SERS sensitivity. Ag clusters are prepared without additional reducing agents, leaving a low carbon footprint in the fabrication process. Finite-difference time-domain (FDTD) simulations show strong electromagnetic field enhancements generated at the edges and interstices of Ag clusters due to the specificity of their structure. Density Functional Theory (DFT) calculations show that the HOMO–LUMO energy gap value is significantly reduced when Ag cluster@rGO forms a composite system with the target molecule, which enables efficient charge transfer between the substrate and molecules, resulting in charge transfer enhancement. A detection limit of 10 −14 M using our substrate can be achieved for the environmental pollutant dye rhodamine 6G (Rh6G). The detection limits of bisphenol A (BPA) and its derivatives reach nanomolar levels with good signal stability. More importantly, we demonstrate the ability to rapidly screen BPA migration in Chinese Baijiu. Our SERS platform can be further developed for environmental pollution control and food safety.